HUBUNGAN MOTIVASI KERJA PERAWAT DENGAN KETEPATAN PENGISIAN DOKUMENTASI ASUHAN KEPERAWATAN DI RUANG RAWAT INAP RSUD BUNTOK 2012 - Berthiana, - (Jurnal Manajemen Keperawatan, 2013)
The accuracy of fill in of the nursing rearing documentation is forms importantthing for nursing services, because will be gives of law protection for the giver and receiver. Nursing rearing will reflection of nursing rearing quality. The accuracy of fill in of the nursing rearing documentation is influenced by motivation. From the study resulted of the nursing rearing applied standard are taken from 30 patient statuses. Can get taken result 61,5%. Who do it the nursing rearing applied standard. This research destination to knowledge related of the nurse work motivation with the accuracy of documentation of the nursing rearing in living medical care installation RSUD Daerah Buntok. The research type id descriptive quantitative with cross sectional approach. Sample for nurse motivVated taken from 4 living medical care unit with total sample 30 respondent, and for theaccuracy of fill in of nursing rearing documentation taken with quota sampling. Taken data with used the questioner, for the accuracy of fill in of nursing rearing documentation use the instrument ASAK from Depkes 1997. For knowing related are two variable, doing with Product Moment Correlation Test with result is rxy = 0,474 and p = 0,008, the meaning is there are have significant related between the nurse work motivation with the accuracy of fill in the nursing rearing documentation in living medical care unit RSUD Daerah Buntok. Work motivated the good nurse so the accuracy of fill in of the nursing rearing documentation is good. The recommendation for another researcher, is important to doing the most deeply research for nurse work motivation with the accuracy of fill in of nursing rearing documentation with another method, more big sample and documentation study with total that will be with SAK rules.Keywords: Nurse motivation, accuracy of fill in of the nursing documentation